Rekonstruksi Independensi Hakim dalam Era Digitalisasi Peradilan Pidana di Indonesia - Firda Laily Mufid; M. Yusuf; Irwan Effendi (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
The advancement of information technology has profoundly transformed the criminal justice system, particularly in judicial proceedings that now utilize digital platforms such as e-court and e-litigation. Although judicial digitalization aims to enhance efficiency and transparency, it simultaneously raises critical concerns regarding judicial independence in the exercise of adjudicative authority. This study employs a normative juridical approach to examine how digital transformation affects the principle of judicial independence and to reconstruct its concept in accordance with the rule of law. The analysis is based on statutory regulations, legal doctrines, and principles governing judicial power. The findings indicate that the integration of technology into judicial processes may create administrative and technological dependencies that potentially undermine the autonomy of judges in deciding criminal cases. Therefore, a redefinition of judicial independence is necessary—one that extends beyond institutional guarantees to include ethical and personal integrity aspects through the reinforcement of judicial accountability and technological transparency. This study recommends the formulation of ethical standards and technical regulations that explicitly limit administrative or external interference with judges in the digital judicial environment, thereby maintaining a balance between technological efficiency and substantive justice.